Religious freedom, LGBT rights, and the prospects for common ground - Eskridge Jr, William N. (Cambridge University Press, 2018)
LGBT, faith, and academic thought-leaders explore prospects for laws protecting each community's core interests and possible resolutions for culture-war conflicts